2009
DOI: 10.1016/j.ijpe.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance practices in Swedish industries: Survey results

Abstract: a b s t r a c tThe purpose of this paper is to investigate the maintenance practices that are used in Swedish industry. The study was performed by conducting a cross-sectional survey within Swedish firms that have at least 100 employees. The main results achieved from the study show that the role of maintenance is not highly recognised. There is a need to spend and invest more in maintenance, which is considered by the majority of Swedish industries as a necessary expense. Although about 13% of the maintenance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 35 publications
3
71
0
6
Order By: Relevance
“…Considering the above explanation, it can be concluded that using appropriate grid policies and activities can considerably influence quality, overall performance, effectiveness, and efficiency of organizational operations, whereby the organization can obtain competitive advantages such as efficiency, long term profitability and value benefits (Alsyouf, 2009). …”
Section: Grid Managementmentioning
confidence: 99%
“…Considering the above explanation, it can be concluded that using appropriate grid policies and activities can considerably influence quality, overall performance, effectiveness, and efficiency of organizational operations, whereby the organization can obtain competitive advantages such as efficiency, long term profitability and value benefits (Alsyouf, 2009). …”
Section: Grid Managementmentioning
confidence: 99%
“…The increasing complexity of the industrial equipments makes it difficult for the users to operate and maintain them. Thus, the maintenance tasks are becoming more and more complex and diverse, involving not only activities on mechanical components, but also on electronic, hydraulic, electromechanical systems, and software (Alsyouf, 2009). As already emphasised, two main types of actions may be distinguished in maintenance: actions for retaining and actions for restoring a service.…”
Section: Industrial Maintenancementioning
confidence: 99%
“…Instead, there may be only a limited number of critical components that is under continuous condition monitoring. For the rest of the components, corrective maintenance and periodic preventive maintenance policies may be in place (see also [1], Section 2.2.1). Hence, it is a challenging problem to coordinate the maintenance actions of the different policies for the various components in a complex system.…”
Section: Introductionmentioning
confidence: 99%